Analysis of the Level of Importance and Ease of Implementing Lean Construction in Building Construction Projects in Aceh Province, Indonesia - Ridal Syathabi; Bulba, Alfa Taras; Anita Rauzana (HM Publisher, 2024)
Lean construction is a construction implementation method that can minimize waste and maximize value. The problem is that there are still many contractor companies that adhere to conventional implementation methods. Lean construction has been introduced by the central government since 2016. This research aims to determine the level of importance and ease of implementation of lean construction on building construction projects in Aceh Province according to perceptions of the qualifications of small and non-small contractor companies partially and simultaneously. Draft Lean construction evaluated as many as 47 indicators. This research uses quantitative methods through questionnaires with a sample of 78 contractor company personnel. Technique sampling used proportionate stratified random sampling. Data analysis techniques used descriptive statistics and importance-performance analysis (IPA). The research results show that in the application of lean construction, according to the perception of small contractor companies, there are 11 indicators that are considered important and not easy to implement. The application of lean construction according to the perception of non-small contractor companies, there are 6 indicators that are considered important and not easy to implement. The application of lean construction according to the perception of small and non-small contractor companies, there are 11 indicators that are considered important and not easy to implement. For small and non-small qualifying contractor companies to increase readiness for implementation of lean construction in building construction projects in Aceh Province, it is necessary to increase the readiness of the indicators included in quadrant A.